Evaluation of Anti-Prion Activity of Congo Red and its Derivatives in Experimentally Infected Hamsters - Poli, Giorgio; Martino, Piera Anna; Villa, Stefania; Carcassola, Gabriella; Giannino, Maria Laura; Dall'Ara, Paola; Pollera, Claudia; Iussich, Selina; Tranquillo, Vito M.; Bareggi, Silvio; Mantegazza, Paolo; Ponti, Wilma (Arzneimittelforschung, 2004)
Among transmissible spongiform encephalopathies (TSE), particularly dreadful are the bovine spongiform encephalopathy (BSE), because of its epidemic character, and the new variant of Creutzfeldt-Jakob disease (vCJD) in man, possibly related to BSE prion, through the intake of infected food. To treat TSE, many potentially therapeutic agents have been tested: some of them, among which is Congo Red (CAS 573-58-0, CR), delayed the onset of symptoms in scrapie-in-fected rodents, and some CR derivatives proved to be effective in vitro.The capacity of a synthesized CR derivative (CR-A) and of the aromatic central benzidine rings of CR (CR-B) to abrogate scrapie-induced disease in experimentally infected hamsters was assayed. CR, used as reference substance, administered i.c. after pre-incubation with the scrapie inoculum, was strongly effective in slowing the progression of the infection, while both CR-A and CR-B, administered alone or together, were not effective. Both CR-A and CR, when administered by subcutaneous route in i.c. scrapie-infected animals, prolonged the survival time in comparison to controls; CR-B was not effective.Moreover, both CR and CR-A were very effective in prolonging the survival time of i.p. scrapie-infected hamsters.The hypothesis of possible different mechanisms of interaction between CR or CR-A and the scrapie agent related to the chemical structures of the molecules is discussed.
Keywords: Bovine spongiform encephalopathy (BSE); CAS 573-58-0; Congo Red, anti-prion activity, derivatives, hamster; Prion protein